Pengaruh Nitrat (NO3) Terhadap Pertumbuhan Alami Eceng Gondok (Eichornia crassipes Solms.) Berdasarkan Biomassa Basah Di Danau Batur, Kintamani, Bali - Prayuda, Lisa Rosalia; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Journal of Marine and Aquatic Sciences; Vol 3 No 2 (2017)DO - 10.24843/jmas.2017.v3.i02.215-222, 2017)
Batur Lake is one of the natural lakes in the province of Bali where the activity of fishing, agriculture, tourism and housing available. This study aims to determine the effect of nitrate relation to the natural growth of the water hyacinth ( Eichornia crassipes ). Increased water hyacinth biomass in Songan station is the highest among the three other stations (Batur, Buahan, and Trunyan). At the end of the study (day 42 ), water hyacinth biomass of Songan station increased by 338.2 % from the initial weight, while at another station the increase weight  ranges from 75 % -158 %. The highest daily growth rate in Trunyan station 3.68% / day, and the lowest in station Buahan which only reached 0.88% / day. At the Songan station where are many floating net which contribute to increase nitrate. There is a tendency of growth of water hyacinth faster at higher nitrate conditions. Nitrate conditions ranged from 0,35 to 0,62 m /l which shows that the waters of Batur Lake classified into waters that have a high fertility rate (eutrophic).